Strategic Portfolio Optimization and Tail-Risk Management: A Comprehensive Single-Index Model Approach Leveraging Risk-Adjusted Metrics in the NIFTY 50 - Chakraborty, Barendra Nath; Kundu, Amit (Southeast Asian Business Review, 2026)
Abstract This study explores the meticulous construction of an optimal portfolio utilizing the Sharpe’s Single-Index. Model (SSIM) for 50 stocks from the NSE NIFTY50 index, spanning data from April 30, 2019, to May 1, 2024. We analyzed key factors such as Beta values, stock variances, and excess returns. This analysis revealed that higher Beta stocks are associated with greater systematic risk, while stock variance primarily influences unsystematic risk. The optimal portfolio, comprising stocks like Apollo Hospitals Enterprise Ltd., Adani Enterprises Ltd., and Asian Paints Ltd., balances risk and return effectively, with Nestle India Ltd., holding the highest weightage. The portfolio Beta of 0.73 suggests lower volatility compared to the market, making it attractive to risk-averse investors. Advanced risk-adjusted performance metrics, including Modified Value at Risk (MVaR), Conditional Expected Drawdown (CED), and the Rachev Ratio (R-Ratio), were utilized to assess tail risk, drawdowns, and the trade-off between extreme gains and losses. This comprehensive analysis provides valuable insights into portfolio optimization, offering a strategic roadmap for investors aiming to maximize returns while managing risk in a volatile market environment.